Pengaruh Kegunaan dan Kemudahan Penggunaan Situs Belanja terhadap Sikap Belanja Online yang Dimoderasi oleh Keahlian dan Kebutuhan untuk Berinteraksi bagi Pengguna Internet - Erminati Pancaningrum; Andriya Risdwiyanto (Universitas Proklamasi 45 Yogyakarta, 2013)
In predicting acceptance of computers by users as a major tool in doing internet access, particularly on access to online shopping, using the measurement scale of the development of the theory of Technological Acceptance Model (TAM). In this study examines the influence of usability and ease of use of online shopping behavior. Also assess the expertise and the need to interact with consumers as a moderator variable in the relationship between usability and ease of use with online shopping attitude. The purpose of this study were (1) analyze the influence of expediency, (2) ease of use of online shopping behavior. (3) Analyze the variables will moderate the influence of expertise whether expediency of online shopping attitudes. (4) Analyze the variables will moderate the influence of expertise whether it easier to interact on online shopping attitudes need to interact. (5) to analyze the variable needs to interact whether to moderate the influence of expediency of online shopping attitudes. (6) to analyze the variable needs to interact whether to moderate the influence of ease of use of online shopping behavior. This research was conducted by taking samples of Internet users in the city of Jombang. The main instrument of data collection in the form of questionnaires and measured with a 5-point Likert scale. Questionnaires were sent to respondents via the internet cafe, free wifi areas, campuses, schools and offices. The number of respondents in this study 122 respondents. Data analysis methods used are Moderated Regression Analysis (MRA). From the analysis it was shown that the variable usefulness and ease of use significantly influences online shopping behavior. Variable expertise to significantly moderate the effect of the use of online shopping behavior, but did not moderate the influence of ease of use of online shopping behavior. While the need for interaction variables did not significantly moderate the effect of usefulness and ease of use of online shopping behavior.